2019
DOI: 10.3390/jcm8030309
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a Standardized Catastrophic Scenario in Virtual Reality or a Personalized Scenario in Imagination for Generalized Anxiety Disorder

Abstract: The cognitive behavioral treatment of generalized anxiety disorder (GAD) often involves exposing patients to a catastrophic scenario depicting their most feared worry. The aim of this study was to examine whether a standardized scenario recreated in virtual reality (VR) would elicit anxiety and negative affect and how it compared to the traditional method of imagining a personalized catastrophic scenario. A sample of 28 participants were first exposed to a neutral non-catastrophic scenario and then to a person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
3
33
0
1
Order By: Relevance
“…Future research should investigate the prevalence of this, and also to test the added benefit of tailored over non-tailored VR exposure scenarios in terms of efficacy. One recent study showed that exposure to standardized VR worry scenarios is equally effective in reducing anxiety as exposure to personalized imagined scenarios (Guitard et al, 2019). Further, most past VRET trials have had limited tailoring capabilities yet still report large effect sizes (Carl et al, 2019;Fodor et al, 2018;Opriş et al, 2012), suggesting that tailoring is not a requirement for effect, although this does not exclude the possibility of larger effects with tailored stimuli material.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate the prevalence of this, and also to test the added benefit of tailored over non-tailored VR exposure scenarios in terms of efficacy. One recent study showed that exposure to standardized VR worry scenarios is equally effective in reducing anxiety as exposure to personalized imagined scenarios (Guitard et al, 2019). Further, most past VRET trials have had limited tailoring capabilities yet still report large effect sizes (Carl et al, 2019;Fodor et al, 2018;Opriş et al, 2012), suggesting that tailoring is not a requirement for effect, although this does not exclude the possibility of larger effects with tailored stimuli material.…”
Section: Discussionmentioning
confidence: 99%
“…As GAD brings several negative effects to patients in many living conditions [40], it is quite difficult to create a scenario of VE that allows people with GAD to relax. To make patients with GAD feel relaxed, the scenarios of VE must be able to reduce many different personalization concerns experienced by patients with GAD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey study on attitudes towards VR among practicing CBT clinicians found that those who worked clinically with neuropsychiatric disorders, personality disorders, and psychosomatic disorders were more inclined to report that VR could be used with the respective disorder (Lindner et al 2019d), suggesting that novel clinical applications of VR are indeed possible. The VR field is currently expanding rapidly, including new research on innovative VR treatments for disorders that have previously received little attention like depression (Migoya-Borja et al 2020;Schleider et al 2019), sleep problems (Lee and Kang 2020), and worry (Guitard et al 2019). Recent work has also studied how VR can be used for modifying cognitions (Silviu Matu 2019) and feared self-perceptions (Wong 2019), in approach-avoidance training for obesity (Kakoschke 2019), and to treat aggressive behavior in children (Alsem 2019), revealing how VR has matured into a flexible, innovative treatment tool.…”
Section: Vr For Other Disordersmentioning
confidence: 99%
“…This question has however received surprisingly little research attention thus far. One recent study compared exposure to standardized catastrophic scenarios in VR, to imaginal exposure with personalized scenarios, and found no difference in evoked anxiety (Guitard et al 2019), suggesting that perfect tailoring is at least not necessary. A study on (360°v ideo) VR relaxation found a strong correlation between averages preference rating of different virtual nature environments and average improvement in positive mood (Gao et al 2019).…”
Section: Full Immersion Through Innovative User Interfaces and Makingmentioning
confidence: 99%